The effect of current thermomodernization projects on energy performance of multi-family residential buildings and perspectives for new regeneration projects: the case of a housing estate in Lublin - Ostańska, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
Managers of large housing estates whose stocks consist mainly of precast concrete plate buildings of 1970ies, due to their sheer size and technical condition far from being perfect, are especially concerned with searching for solutions that would reduce energy consumption. Thermal modernization projects provide an opportunity to adopt a holistic approach to the problem of obsolescence of this relatively new housing stock and to consider it in terms of urban regeneration. The paper describes the energy saving policies in Poland and results of pilot studies of Building Research Institute (ITB) aimed at defining optimal scope of thermomodernization of precast concrete plate housing. The paper investigates into the effects of thermomodernization of a particular, though typical, housing estate in Lublin in order to give grounds for future actions in the field of energy saving measures.